1997
DOI: 10.1046/j.1365-2648.1997.1997025562.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and quality of life in the renal transplant patient: a preliminary investigation

Abstract: End-stage renal disease is a chronic condition which reduces the life-span of its victims. At present there is no cure. Renal transplantation, currently the treatment of choice for many patients, is potentially associated with a number of drawbacks: constant risk of rejection, especially during the first six months, the need to comply with a complex regime of medication capable of producing pronounced side-effects and need for ongoing medical supervision. Despite these problems, little research has been undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 20 publications
8
86
1
3
Order By: Relevance
“…2 Even with a well-functioning graft, these individuals continue to be chronic disease patients who are subject to some level of social, physical and emotional limitations, as is the case with dialysis patients. 9,[22][23][24][25] However, differently from our study, most other studies failed to directly assess the frequency of stress.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…2 Even with a well-functioning graft, these individuals continue to be chronic disease patients who are subject to some level of social, physical and emotional limitations, as is the case with dialysis patients. 9,[22][23][24][25] However, differently from our study, most other studies failed to directly assess the frequency of stress.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, previous studies evaluating stress and kidney transplantation have used other instruments such as scales based on subjective measurement of stressful factors or specific life themes, including those relating to the illness. [22][23][24][25]28 Those scales probably have limited evaluation capacity because they rely on patient memory and do not consider the coping strategies used by patients, which may alter the stress results. 35 Additionally, we did not find any studies that have shown any consistent link between the specific phases of stress and nonadaptive behavior of nonadherence in cases of kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…64 We found no statistically significant association between the number of detected ADRs and immunosuppressive regimens with or without mycophenolate mofetil (P = .629). Inasmuch as the number of patients who developed nausea and vomiting, diarrhea, nephrotoxicity, hepatotoxicity, or thrombocytopenia was limited in the current survey (9,8,6,5, and 4 subjects), comparing the effect of different immunosuppressive regimens on the prevalence of these ADRs was not statistically feasible.…”
Section: Discussionmentioning
confidence: 90%
“…14 Likewise, severe adverse effects of immunosuppressive therapy are known to affect treatment compliance, which in turn adversely affects the patients' physical and psychological well-being. 15 Studies based on the theory of stress and response have shown that the adverse effects of immunosuppressive treatment and economic hardships are major stressors for kidney transplant recipients, 16,17 and severely affected patients are likely to adopt negative coping mechanisms. 18 In this cross-sectional study, we assessed the health-related quality of life of living-donor kidney transplant recipients and examined the response of patients to various stressors.…”
Section: Introductionmentioning
confidence: 99%